A Fully Dynamic Algorithm for Planar Width - Chan, Timothy M. (Discrete & computational geometry, 2003)
We show how to maintain the width of a set of n planar points subject to insertions and deletions of points in O(([root]n)log3n) amortized time per update. Previously, no fully dynamic algorithm with a guaranteed sublinear time bound was known. [PUBLICATION ABSTRACT]